The sleeping nymph - Tuti, Ilaria ([The Teresa Battaglia novels], 2020)
"A decades-old murder investigation has landed on Superintendent Teresa Battaglia's desk. DNA analysis has revealed that a painting from the final days of World War II contains matter from a human heart. Teresa is able to trace the evidence to Val Resia, one of Italy's most isolated, untouched regions. When Teresa's investigation hits too close to the truth, a second human heart is hung at the valley's entrance, a warning not to cross its threshold. Meanwhile, Teresa must not only deal with rapidly progressing physical and cognitive ailments, but also someone she hoped never to see again-a man who is now her supervisor"--